Front Cover Picture: Auto‐Tandem Catalysis‐Induced Synthesis of Trisubstituted Furans through Domino Acid‐Acid‐Catalyzed Reaction of Aliphatic Aldehydes and 1, 3‐Dicarbonyl Compounds by using N‐Bromosuccinimide as Oxidant (Adv. Synth. Catal. 11/2017). Issue 11 (21st March 2017) - Huang, Wenbo; Liu, Changhui; Gu, Yanlong
Abstract : Thefront cover picture, provided by Yanlong Gu and co‐workers, illustrates the development of a method to synthesize 2, 3, 5‐trisubstituted furans from two readily available precursors, aliphatic aldehydes and 1, 3‐dicarbonyl compounds. This method was established on the basis of using N ‐bromosuccinimide as an oxidizing reagent and aluminum(III) chloride as a catalyst. An acid‐acid‐catalyzed tandem reaction with auto‐tandem catalysis was involved in the reaction mechanism. Details can be found in the communication on pages 1811–1818 (W. Huang, C. Liu, Y. Gu, Adv. Synth. Catal .2017, 359, 1811–1818; DOI:10.1002/adsc.201700074 ).